Defenition of topological space of the Іnternet - Mokhor, V.V.; Zubok, V.Yu. (Problems of Informatization and Management, 2021)
A topology of a computer network is a method of organization or mutual arrangement of its elements determined by its architecture, which includes all types of network devices (end devices, switches, routers, extension cords, etc.) and its own connection. Since it is known that the Internet is a union of computer networks, and its essence is in this union on the principles of general logical addressing and routing, it is worth considering the "topology of the Internet" at the logical level, which describes data flows. The lack of a specific definition of the Internet topology as a concept, and, at the same time, the study of the Internet topology, is a contradiction that is an obstacle to finding ways to improve the network and protect against cyber-attacks, including its global routing system. Therefore, a variant of formulating the concept of "Internet topology" through the mathematical definition of the topological space of the global computer network Internet, which is formed by a global routing system on a set of connections between nodes – autonomous systems. It is also shown that routes that carry information about the availability of network prefixes are elements of the topology. This opens the way to the use of topology methods to study the topological space of the Internet.